Hippocampal and amygdalar cell‐specific translation is similar soon after stress but diverge over time. Issue 6 (June 2018) - Madan, Jesvin S.; Gupta, Kanika; Chattarji, Sumantra; Bhattacharya, Aditi
Abstract: Stress is known to cause contrasting patterns of morphological and physiological plasticity in the hippocampus and amygdala. An obligatory cellular process underlying such neural changes is de novo translation and alterations in protein expression. Yet the nature of the translational response to stress in neurons remains largely unexplored. Even less is known about how glia are affected. Using a click‐chemistry‐based method to label the de novo proteome in live brain slices, we monitored translation in neurons and astrocytes of the basolateral amygdala (BLA) and dorsal hippocampal area CA3 (dCA3) in rats at different time‐points after a single 2‐hr exposure to immobilization stress. We observed enhancements in neuronal translation in both brain regions 1 hour after stress. This initial increase persisted in the BLA up to 10 days afterwards. In contrast, dCA3 neuronal translation gradually decreased to below control levels 10 days later. Translation profiles of dCA3 astrocytes followed timelines similar to neurons, but in BLA astrocytes translation peaked 1 day later and remained elevated 10 days later. Together our results demonstrate that stress causes an immediate upregulation of protein synthesis in both amygdalar and hippocampal neurons and astrocytes. However, these two areas eventually exhibit opposite temporal profiles of protein expression well after the end of stress. These findings identify new metrics of stress‐induced plasticity at the level of cell‐type specific proteomic landscape that may provide important insights into the molecular basis of the divergent temporal effects of stress across brain regions and biological scales.